Comparative Study of Choke Vessel Reconstruction With Single and Multiple Perforator–Based Flaps on the Murine Back Using Delayed Surgery. Issue 1 (January 2019) - Mao, Yihua; Li, Hong; Ding, Maochao; Hao, Xiaodi; Pan, Jing; Tang, Maolin; Chen, Shixin
Abstract : Objective: Choke vessels, vascular anastomosis between adjacent angiosome, play an important role in flap expansion and survival. Here we established a flap model with single and multiple perforators to detect and compare the changes in choke vessels, discuss the effect of hemodynamics on the vascular morphology, and explore the underlying mechanism. Methods: One hundred mice (7–8 weeks) were subjected to a "choke zone" surrounded by 4 perforators on their backs. Delayed surgery was performed by the ligation of 1, 2, or 3 perforators to establish flap models. The blood flow of the choke zone was measured by laser Doppler flowmetry preoperatively and 6 hours and 1, 3, 5, and 7 days. The morphological changes of choke vessels in the choke zone were observed by gross and histological analyses. Levels of angiogenesis-related markers such as endothelial nitric oxide synthase (eNOS), metalloproteinase 2, hypoxia-inducible factor 1α (HIF-1α), and intercellular adhesion molecule 2 (ICAM-2) were detected by Western blotting and enzyme-linked immunosorbent assay. Results: Blood flow and microvascular count were obviously increased postoperatively and peaked and were maintained for 1 week ( P < 0.01). Meanwhile, the diameters of the choke vessels expanded. The eNOS level was increased at 7 days ( P < 0.05); however, the enzyme-linked immunosorbent assay results showed that the HIF-1α and ICAM-2 levels were decreased at 7 days. Conclusions: (1) The delayed surgery that kept a single perforator had the greatest impact on the choke zone. (2) Changes in choke vessels were closely related to the shear stress caused by enhanced blood perfusion after surgery. (3) Choke vessel growth was regulated by eNOS, metalloproteinase 2, HIF-1α, and ICAM-2.